PHARMACOLOGY OF ANTIDEPRESSANT DRUGS (LITERATURE REVIEW) - Djanaev G.Yu; Mustanov T.B; Kakhkharova Sh.B (Scientific Impulse, 2024)
This review covers mechanisms of action, efficacy, side effects, and toxicity of various classes of antidepressants:tricyclic antidepressants, monoamine oxidase inhibitors, second-generation antidepressants including the selective inhibitors of serotonin reuptake, and novel drugs such as mirtazapine, nefazodone, and venlafaxine. After the clinical aspects of depression are introduced in this article, the pharmacology of the newer generation drugs is reviewed in relationship to the older compounds. The information in this review will help clinicians treat acute depression with pharmacological agents. Despite extensive research to find a diagnostic test, the diagnosis of depression remains clinical. The criteria for the diagnosis of major depression5 are the core signs and symptoms, including depressed mood, diminished pleasure or interest in activities, pronounced change in appetite or weight, alterations in sleep (insomnia or hypersomnia), psychomotor agitation or retardation, fatigue or loss of energy, inability to concentrate, indecisiveness, and thoughts of death, dying, or suicide. When fewer antidepressant compounds were available, the drugs were classified either as tricyclic antidepressants or as monoamine oxidase inhibitors (MAOIs), a classification that mixes a structural criterion with a functional one. At present, a broad range of structures make up the antidepressant pharmacopoeia, but there are only a few known functional (possibly therapeutic) effects of these compounds. Therefore, a functional classification of antidepressants is more useful than a structural.